PERILAKU KONSUMEN DALAM BELANJA ONLINE MELALUI PERSPEKTIF GENDER - Ahmad Nurdin Hasibuan; Delila Rambe (Mediastima, 2020)
The current business competition has encouraged business managers (as well as business candidates) to move quickly, creatively and anticipatively. This is due to a fundamental change in business competition systems that utilize technology. These changes include trading systems, transactions, marketing systems and payment systems. Agreements on free trade have resulted in various products flowing swiftly from one country to another without barriers or protection. The results showed that respondents' assessment of the implementation of online shopping attitudes, ease of transactions in purchasing decisions on alternative options is very good. The analysis shows that the value of 0.750 means the attitude of online shopping and the perception of ease of transactions have a close and positive correlation to the purchasing decision of respondents. While the influence of the attitude of online shopping and the perception of ease of transactions on the purchase decision of respondents 56.30%. while the remaining 43.70% again influenced by other factors.